Correction: IFI16 Restricts HSV-1 Replication by Accumulating on the HSV-1 Genome, Repressing HSV-1 Gene Expression, and Directly or Indirectly Modulating Histone Modifications. - Karen E Johnson; Virginie Bottero; Stephanie Flaherty; Sujoy Dutta; Vivek Vikram Singh; Bala Chandran (PLoS Pathogens, 2018)
[This corrects the article DOI: 10.1371/journal.ppat.1004503.].